Adjunctive therapy for the treatment of primary generalized tonic-clonic seizures: focus on once-daily lamotrigine - Linda Steinbaugh; Jerzy P Szaflarski (Dove Medical Press, 2010)
Linda Steinbaugh, Jerzy P SzaflarskiDepartment of Neurology and Cincinnati Epilepsy Center, University of Cincinnati Academic Health Center, Cincinnati, Ohio, USAAbstract: Idiopathic generalized epilepsies are frequently encountered by neurologists, and providing an accurate diagnosis and effective treatment(s) are the necessary components of successful patient care. With the introduction of new antiepileptic medications, physicians are better equipped for this goal. The immediate-release formulation of lamotrigine (LTG-IR) has been approved for primary generalized tonic-clonic seizures since 2006. The extended-release formulation of lamotrigine (LTG-XR) was approved for adjunctive therapy in patients with primary generalized tonic-clonic seizures in 2010. Although its exact mechanism of action is not yet fully elucidated, studies have demonstrated multiple possible pathways. Although both the LTG-IR and LTG-XR formulations have similar side effects and are generally well tolerated, LTG-XR may be preferable for its ease of use, which may increase patient compliance and decrease fluctuations in serum drug levels. The ease of conversion between the formulations also makes lamotrigine an attractive treatment option for patients with primary generalized tonic-clonic seizures. LTG-IR has demonstrated efficacy in treatment-resistant idiopathic generalized epilepsies in both adults and children. Although there are still some questions regarding all possible applications of LTG-XR, as further research is being done, it is clear that LTG-XR may hold some advantages when compared with other anticonvulsants.Keywords: lamotrigine, GTC, IGE, generalized seizures, treatment